2k-1=-5+3k

Simple and best practice solution for 2k-1=-5+3k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2k-1=-5+3k equation:


Simplifying
2k + -1 = -5 + 3k

Reorder the terms:
-1 + 2k = -5 + 3k

Solving
-1 + 2k = -5 + 3k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-3k' to each side of the equation.
-1 + 2k + -3k = -5 + 3k + -3k

Combine like terms: 2k + -3k = -1k
-1 + -1k = -5 + 3k + -3k

Combine like terms: 3k + -3k = 0
-1 + -1k = -5 + 0
-1 + -1k = -5

Add '1' to each side of the equation.
-1 + 1 + -1k = -5 + 1

Combine like terms: -1 + 1 = 0
0 + -1k = -5 + 1
-1k = -5 + 1

Combine like terms: -5 + 1 = -4
-1k = -4

Divide each side by '-1'.
k = 4

Simplifying
k = 4

See similar equations:

| 24x=24+7x | | -3(4p+4)-2(6-14p)-3(7+5p)=0 | | 2(-5U+10)+2u= | | 2-5a=-8 | | 7x+5x-38=95-7x | | 2k-1=-5+2k | | 5b-13=3b+1 | | t=6s+18.01 | | 5z+30=40 | | 5-3p+9=13p+8 | | 3f+2=5 | | 5-4p=11 | | (5x-1)(x-5)=0 | | 0=324+2*3.65*x | | 9-(x+6)=9x-7 | | 0.3x-2.9=4.7x+2.6 | | 9x^4-25x^3+16x^2=0 | | 4n+5n=27 | | -2x^2+17x-35=0 | | (10x-10)=(8x+14) | | -8+3r=-3+2r | | 6+x+6+x=6x | | -8x+11+9x=2+x+9 | | 10r=4r+12 | | 15-(3m-5)=32 | | t+10=7r-14 | | X-4=4-3x | | (C+8)x-3y+7=0 | | 18=-7x+50 | | 5t+16=2p+112 | | 7x-5-6x=0 | | 3b+3=2b+9 |

Equations solver categories